Ernst Rüdin's, 1911 vision of a Mendelian psychiatric genetics research program: His paper “Methods and goals of family research in psychiatry” - Kendler, Kenneth S. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2021)
While working under Kraepelin in Munich, Ernst Rüdin, a Swiss‐born Psychiatrist, at the age of 26, outlined in a 1911 98‐page article, a detailed plan for a future Mendelian‐informed family research program for psychiatry. Rüdin would go on to head the Department of Genealogical and Demographic Studies at Kraepelin's Research Institute which became one of the world's leading programs in psychiatric genetics. I here summarize this article, providing a complete translation online. Rüdin's review outlined a paradigm shift in psychiatric genetics research moving from calculations of aggregate hereditary burden, as they applied to the proband, to examining patterns of transmission within family pedigrees which involved careful individual assessments of relatives. He references widely clinical and statistical genetic studies, many focusing on the newly discovered Mendelian laws. However, Rüdin was no genetic reductionist but recognized the contribution of environmental risk factors to psychiatric illness arguing that they should be studied as part of a comprehensive research program. As a committed eugenicist, Rüdin also explored the implications of such a program for “racial hygiene.” Rüdin's contributions should be viewed in the context of his extensive collaboration from 1933 to 1945 with the National Socialists and his support for their eugenics program, including involuntary sterilizations.